2021
DOI: 10.1037/tam0000165
|View full text |Cite
|
Sign up to set email alerts
|

TRAP-18 indicators validated through the forensic linguistic analysis of targeted violence manifestos.

Abstract: This study is a qualitative and quantitative analysis of written and spoken manifestos authored by lone offenders that planned to or committed a targeted attack (n = 30). The acts of violence were primarily motivated by an ideology or a personal grievance, and occurred between 1974-2021. The main objective of this retrospective study was to examine if a behavior-based threat assessment instrument, the Terrorist Radicalization Assessment Protocol (TRAP-18), could be applied to a thin slice of data using only la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 42 publications
0
53
1
Order By: Relevance
“…Both Bronsard and colleagues (2022) and Lyons and Harbinson (1986) report on point-prevalence rates of diagnosed disorder (at time of assessment) based on clinical interview. The remaining papers F I G U R E 12 Forest plot of studies reporting lifetime rates of psychological problems where problems were onset before detection or involvement F I G U R E 13 Forest plot of studies reporting lifetime prevalence rates of any mental health difficulties where these were onset before detection or involvement reporting on life-time prevalence based on research interview (Dhumad et al, 2020) or open-source data (Capellan 2015;Capellan & Anisin, 2018;Capellan et al, 2019;Kupper & Meloy, 2021).…”
Section: Included Studiesmentioning
confidence: 99%
“…Both Bronsard and colleagues (2022) and Lyons and Harbinson (1986) report on point-prevalence rates of diagnosed disorder (at time of assessment) based on clinical interview. The remaining papers F I G U R E 12 Forest plot of studies reporting lifetime rates of psychological problems where problems were onset before detection or involvement F I G U R E 13 Forest plot of studies reporting lifetime prevalence rates of any mental health difficulties where these were onset before detection or involvement reporting on life-time prevalence based on research interview (Dhumad et al, 2020) or open-source data (Capellan 2015;Capellan & Anisin, 2018;Capellan et al, 2019;Kupper & Meloy, 2021).…”
Section: Included Studiesmentioning
confidence: 99%
“…Eleven empirical studies were identified which utilized the TRAP-18 to retroactively evaluate terrorist incidents (Böckler et al, 2021; Brugh et al, 2020; Challacombe & Lucas, 2019; García-Andrade et al, 2019; Goodwill & Meloy, 2019; King et al, 2018; Kupper & Meloy, 2021; Meloy & Gill, 2016; Meloy, Roshdi, et al, 2015; Meloy et al, 2019, 2021). See Table 4, for descriptive information and findings for each of the 11 empirical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six case studies were identified which utilized the TRAP-18 retroactively (Böckler et al, 2015; Böckler et al, 2017; Collins & Clark, 2021; Erlandsson & Reid Meloy, 2018; Meloy, Habermeyer, & Guldimann, 2015; Meloy & Genzman, 2016). Eleven studies were identified which utilized the TRAP-18 to retroactively evaluate terrorist incidents (Böckler et al, 2021; Brugh et al, 2020; Challacombe & Lucas, 2019; García-Andrade et al, 2019; Goodwill & Meloy, 2019; King et al, 2018; Kupper & Meloy, 2021; Meloy et al, 2019; Meloy & Gill, 2016; Meloy, Roshdi, et al, 2015; Meloy et al, 2021). All studies in this review involved TRAP-18 indicators being assessed and coded based on past events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations